Approaches and perspectives on the transition to the circular economy in the European Union - Georgescu, Lucian Puiu; Barbuta Misu, Nicoleta; Antohi, Valentin Marian; Fortea, Costinela; Zlati, Monica Laura (Frontiers in Environmental Science, 2025)
IntroductionThe transition to a circular economy is a key pillar of European sustainable development. However, in the current context, shaped by multiple crises and geopolitical conflicts, the efficiency and resilience of this transition are of particular concern. European policymakers and national authorities must adapt their approaches to mitigate risks posed by external factors while ensuring progress towards European sustainability goals. This study analyzes the transition to the European circular economy from 2010 to 2022, assessing key economic and environmental variables.MethodsThe study employs an econometric approach using panel data from the 27 EU Member States. A multiple linear regression model with fixed effects panel data is applied alongside spectral analysis and descriptive statistics to examine the relationships between private investment, gross value added, municipal waste recycling rates, recyclable material flows, and greenhouse gas emissions. These methods allow for an in-depth evaluation of the factors influencing the efficiency of the circular economy transition.ResultsFindings indicate that private investment and the integration of recyclable materials significantly enhance the efficiency of the circular economy. However, progress varies across Member States due to regional disparities, inadequate recycling infrastructure, and inefficient municipal waste management. High-emission countries face greater challenges in achieving environmental targets, demonstrating the need for tailored and resilient policy measures.DiscussionThe results highlight the necessity of public policies that promote the attractiveness of circular economy sectors, reduce regional disparities, and improve waste management infrastructure. Additionally, the study emphasizes the importance of a coordinated and region-specific approach to accelerate the transition towards a sustainable circular economy. By integrating seasonal and regional analyses, the research contributes to the literature by offering a nuanced understanding of the factors affecting circular economy progress. These insights are valuable for supranational policymakers in developing effective strategies to enhance circular economy resilience at the European level.